Effects of ambient temperature, energy density, and energy source on energy partition and plasma metabolomics profile of finishing pigs - Dan Jiang; Kai Zhou; Dongsheng Che; Hailong Jiang; Rui Han; Guixin Qin (Animal Nutrition, 2025)
Ambient temperature is an important factor affecting metabolic processes in animals, and its effect on energy metabolism is becoming more evident. Yet, integrative analysis of energy metabolism in finishing pigs at different combinations of ambient temperature, energy density and energy sources, still remain underexplored. In order to determine the special characteristics of energy metabolism of finishing pigs in low-temperature environment, the effects of different combinations of ambient temperature, energy density, and energy source on underlying mechanisms were elucidated by assessing energy metabolism using integrative indirect calorimetry and non-targeted plasma metabolomics analyses. Thirty-two finishing pigs (Duroc × Large White × Landrace) with similar body weight of 85.44 ± 2.04 kg were allotted in a 2 × 2 × 2 factorial arrangement (8 treatment groups, 4 replicates per group, 1 pig per replicate), which included two ambient temperatures (low temperature [10 °C] and normal temperature [20 °C]), two energy densities (normal energy density [NE, 14.02 MJ/kg] and high energe density [HE, 15.14 MJ/kg]), and two energy sources (low-oil source and high-oil source). The experiment period lasted 11 days. Increasing the energy density of the diet by adding oil changed the energy source in a low-temperature environment, improved crude fat digestibility (P < 0.001), and reduced the feed/gain ratio of pigs (P = 0.004), with a tendency for higher average daily gain (P = 0.098), which would increase energy utilization. Adding oil to the diet altered energy sources at low temperature, reducing carbon dioxide emission by 3.10%, increasing energy retention and fat oxidation (P < 0.05). Further, optimizing energy sources by adding oil significantly improved serum glucose (GLU) content (P < 0.001) and reduced urea nitrogen (UN) content at normal temperature (P < 0.001), with the same trend observed at low temperature. The metabolites in the eight groups were mainly enriched in the sphingolipid signaling pathway, insulin resistance, and glycerophospholipid metabolism (P < 0.05). Energy metabolism in finishing pigs was not only affected by ambient temperature and energy density, but also by energy source, leading to variations in metabolic pathways for different energy substances. Increasing the dietary energy density by increasing oil supplementation at low temperature is an effective way to improve the growth performance of finishing pigs while reducing pollutant emissions. The study provides a new solution for optimizing energy nutrition for finishing pigs in low-temperature environment.